Deteriorating patients and risk assessment among nurses and junior doctors: a review - Mohamed Ludin, Salizar; Ruslan, Rusila; Mat Nor, Mohd Basri (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
The presence of nurses and junior doctors in the ward environment are crucial, especially in detecting deteriorating patients. However, there is consistent evidence that warning signs may not always be identified or acted upon. This paper aimed to analyse the incidence of deteriorating patients, and the concept of risk assessment of these patients by nurses and junior doctors in general ward, through a review on relevant literature. An extensive literature search was conducted through online research databases, i.e. CINAHL, MEDLINE (Ovid), Science Direct and ProQuest. Professional journals were hand searched for relevant literature based on reference lists and citations made in key publications, and attempts were also made to obtain any relevant grey literature (unpublished materials). A total of eleven papers which focused on patient’s assessment, response to deteriorating patients and knowledge in medication, and a guideline were reviewed. Most of the studies were carried out in the United Kingdom (n=4), followed by Australia (n=2), Sweden (n=2), the Netherlands (n=1) and Taiwan (n=1). Meanwhile, among these studies, the chosen research designs include, qualitative (n=6), quantitative (n=3) and systematic review (n=1). This review concluded that nurses and junior doctors in general ward have a lack of knowledge in risk assessment of deteriorating patients.